EFFECT OF VARIOUS CRYOPROTECTANTS ON PRESERVATION OF BLACK TIGER Penaeus monodon SHRIMP SPERMATOZOA - Rosmiati Rosmiati; Ike Trismawanti; Samuel Lante (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2020)
The development of cryopreservation technique on tiger shrimp Penaeus monodon broodstock spermatophore has been carried out to support the artificial insemination. This study aims to determine the effect of three cyoprotectants (methanol, dimetylsulphoxide (DMSO), and glycerol) for long term storage of tiger shrimp Penaeus monodon spermatozoa. Spermatophores were collected from the wild broodstocks through electrical shock. Spermatozoa were obtained by homogenizing the spermatophores using a Radnoti micro homogenizer in Ca-free saline solution containing one of three cryoprotectans (methanol, dimetylsulphoxide, and glycerol) separately at the concentration of 5%. One mL of each cryoprotectant containing spermatozoa with the density of 1.02 x 106 cell/mL was transferred into a cryovial and cryopreserved at room temperature, -20°C and -196°C for 5, 10, and 30 days. The apparent sperm viability (ASV) of cryopreserved spermatozoa was monitored after treated. Thawing of cryopreserved spermatozoa was carried out in a 30°C wáter bath for two minutes. The result showed that the best apparent sperm viability was obtained at the using of glycerol at -196°C in liquid nitrogen, even after the thirty days of cryopreservation time period with the ASV of 0.82 x 106 cells/mL (80.39%). Meanwhile two other cryoprotectans displayed the ASV of 0.54 x 106 cells/mL (56.86%), and 0.23 x 106 cells/mL (22.55%). for DMSO and methanol, respectively. In turn, the control showed the lowest ASV with the ASV of 0.01 x 106 cells/mL (1.27%). The ASV showed by this glycerol exhibited asignificant difference (P<0.05) to that of methanol, DMSO, and control.